RESILIENCE AS A PROFESSIONALLY IMPORTANT QUALITY OF PRACTICAL PSYCHOLOGISTS: A CONTEMPORARY SCIENTIFIC PERSPECTIVE - Kravchuk, Vladyslav (Personality and environmental issues, 2026)
The article presents a theoretical analysis of resilience as a professionally important quality of practical psychologists. Contemporary scientific approaches to understanding resilience are examined, including trait-oriented, process-oriented, and socio-ecological perspectives. Particular attention is devoted to the role of resilience in maintaining professional effectiveness, psychological well-being, and occupational sustainability among practical psychologists. The relationship between resilience and occupational stress, secondary traumatic stress, compassion fatigue, and professional burnout is analyzed. Contemporary research demonstrates that resilience functions as a multidimensional psychological resource incorporating emotional, cognitive, behavioral, and social components. Theoretical evidence indicates that resilience contributes to adaptive functioning, professional competence, and maintenance of psychological health among helping professionals. The significance of resilience for psychologists working under conditions of social instability and military conflict is substantiated. The necessity of developing resilience through professional education, supervision, and continuing professional development is emphasized.